Influence of Promotion Mix on Consumer Purchase Intention Towards Umrah and Hajj Travel Agency Service (Study Case of Haromain Mubarok Tour and Travel) (Journal of Business and Management, 2021)
Indonesian SMEs are on the rise, streak from 52 million in 2010 and expected to reach 65 million by 2020. Umrah and hajj travel agency is one of examples, since Indonesia has the largest Muslim population and always been ranked as top 10 countries sending the most umrah and hajj pilgrims with 988 existing agencies. Ironically, SMEs still face marketing problems especially in promotion area. Therefore, it is important to identify the potential market and understand the influence of promotion mix tools towards purchase intention. Research is done in Bandung through questionnaire with 205 respondents and analyzed using multilinear regression. It is discovered that advertising, personal selling, and sales promotion have the strongest influence, while public relations and direct marketing are the weakest. Additionally, people aged 22 up to ?56 years old with monthly income IDR ?1.000.000 up to ?10.000.000 regardless their gender, education, occupation, and umrah or hajj experience are indeed a potential market. Hence, it is suggested to approach the potential market using advertising, personal selling, and sales promotion in order to increase their intention to purchase umrah and hajj travel service. But the strategy needs to be adjusted to fit in every segment of the potential market. Keywords: Consumer Purchase Intention, Indonesian SMEs, Marketing Strategy, Promotion Mix, Umrah and Hajj Travel Service